2021
DOI: 10.18632/oncotarget.27974
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic cellular biomechanics in responses to chemotherapeutic drug in hypoxia probed by atomic force spectroscopy

Abstract: The changes in cellular structure play an important role in cancer cell development, progression, and metastasis.By exploiting single-cell, force spectroscopy methods, we probed biophysical and biomechanical kinetics (stiffness, morphology, roughness, adhesion) of brain, breast, prostate, and pancreatic cancer cells with standard chemotherapeutic drugs in normoxia and hypoxia over 12-24 hours. After exposure to the drugs, we found that brain, breast, and pancreatic cancer cells became approximately 55-75% less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…4,5 Recent studies of cellular biomechanics have demonstrated the remarkable difference in biomechanical properties (e.g., stiffness, morphology, roughness, adhesion) between cancer cells, as well as their response to the chemotherapy drugs in hypoxia. 6 In particular, cancer cells increase the expression of membrane proteins and receptors for amplifying cell-to-cell signaling and cell-to-extracellular matrix (ECM) adhesion. Thus, the distinct expression patterns and levels of plasma membrane proteins have been identified as one of the most promising biomarkers for cancer diagnosis and attractive candidates for membrane-targeted anticancer drug development and delivery.…”
Section: ■ Introductionmentioning
confidence: 99%
“…4,5 Recent studies of cellular biomechanics have demonstrated the remarkable difference in biomechanical properties (e.g., stiffness, morphology, roughness, adhesion) between cancer cells, as well as their response to the chemotherapy drugs in hypoxia. 6 In particular, cancer cells increase the expression of membrane proteins and receptors for amplifying cell-to-cell signaling and cell-to-extracellular matrix (ECM) adhesion. Thus, the distinct expression patterns and levels of plasma membrane proteins have been identified as one of the most promising biomarkers for cancer diagnosis and attractive candidates for membrane-targeted anticancer drug development and delivery.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These results are in line with our previous study addressing that alteration in the mechanotransduction cascade of post-treated with anti-tumor agents cells that became stiffer had also a limited tendency for cell motility and restricted potential in migration [ 16 ]. Furthermore, the increased post treatment cell membrane roughness of MCF-7 cells in combination with F-actin reorganization in both static and dynamic conditions contributes also to a stiffer cell with limited cell motility as previous studies established [ 32 , 33 ]. Similar morphology of MCF-7 cells with reduced membrane ruffles, pseudopodia, and lamellipodia was detected in the study of Flamini et al, post treatment with retinoic acid, indicating a restricted migratory phenotype [ 34 ].…”
Section: Discussionmentioning
confidence: 61%
“…Figure 1D demonstrates various applications of bio-AFM (Hoh and Hansma 1992;Shao and Yang 1995;Czajkowsky et al, 2000;Hansma 2001;Goldsbury and Scheuring 2002;Malkin et al, 2002;Alonso and Goldmann 2003;Besch et al, 2003;Gadegaard 2006;Shahin and Barrera 2008;Goldsbury et al, 2009;Ramachandran et al, 2011;Kreplak 2016;Dufrene et al, 2017;Braet and Taatjes 2018;Gao et al, 2018;Cheong et al, 2019;Nandi and Ainavarapu 2021), and we are about to summarize these in this review. Unlike the AFM imaging modes where the probe is scanned over the surface of the substrate, the cantilever tip is first approached toward the substrate until tip-sample contact happens and then retracted in AFM dynamic force spectroscopy (AFM-DFS) (Sulchek et al, 2005;Neuert et al, 2006;Thormann et al, 2006;Diezemann and Janshoff 2008;Alessandrini et al, 2012;Sengupta et al, 2014;Sluysmans et al, 2018;Ju 2019;Reiter-Scherer et al, 2019;Alhalhooly et al, 2021) and single-molecule force spectroscopy (AFM-SMFS) experiments. These two are similar methods with slight differences.…”
Section: Introductionmentioning
confidence: 99%